The earl next door - Grey, Amelia (First comes love, 2019)
When Adeline, Dowager Countess of Wake, learns of her husband<U+2019>s sudden death, she realizes she<U+2019>s free. At last, she can do, go, and be as she pleases. Finally, she can have the life she has always dreamed of. She doesn<U+2019>t need, or want, to remarry. Especially not the supremely dashing future Marquis of Marksworth, who makes Adeline yearn for his desire. . . Lord Lyonwood, son of a philandering marquis, will not be like his father. He wants to run his estates and watch them flourish<U+2015>and find a wife who brings love to his life. When he meets spirited and self-reliant Adeline in a case of near-scandalous mistaken identity, Lyon feels he<U+2019>s met his match. But Adeline isn<U+2019>t interested in a marriage proposal. She will only accept becoming his lover<U+2015>and Lyon finds it hard to refuse. Unless the fire of his passion can melt Adeline<U+2019>s resolve. . .